Understanding place attachment through the lens of urban regeneration. Insights from Lisbon - Falanga, Roberto (2022)
Scholarly debate on the role of place attachment in urban regeneration has been surprisingly limited. Despite the spread of regeneration policy schemes worldwide, little is known about the interplay of place memory, changes, and community action – three main components of place attachment – through the regeneration of deprived urban areas. To fill this gap, this Brief Communication presents and discusses the main findings retrieved from the investigation developed in Lisbon between 2017 and 2020. My main argument is that place memory is a positive precondition for internally driven changes through spontaneous community action developed in popular spaces of participation. In contrast, externally driven changes lower people's sense of control, and invited spaces of participation equally hinder the potential of place attachment for urban regeneration.